Structural control of highly efficient thermally activated delayed fluorescence in carbene zinc(II) dithiolates - Mitra, Mousree; Mrózek, Ondřej; Putscher, Markus; Guhl, Jasper; Hupp, Benjamin; Belyaev, Andrey; Marian, Christel M.; Steffen, Andreas (Technische Universität Dortmund, 2023)
Luminescent metal complexes based on earth abundant elements are a valuable target to substitute 4d/5d transition metal complexes as triplet emitters in advanced photonic applications. Whereas CuI complexes have been thoroughly investigated in the last two decades for this purpose, no structure-property-relationships for efficient luminescence involving triplet excited states from ZnII complexes are established. Herein, we report on the design of monomeric carbene zinc(II) dithiolates (CZT) featuring a donor-acceptor-motif that leads to highly efficient thermally activated delayed fluorescence (TADF) with for ZnII compounds unprecedented radiative rate constants kTADF=1.2×106 s−1 at 297 K. Our high-level DFT/MRCI calculations revealed that the relative orientation of the ligands involved in the ligand-to-ligand charge transfer (1/3LLCT) states is paramount to control the TADF process. Specifically, a dihedral angle of 36–40° leads to very efficient reverse intersystem-crossing (rISC) on the order of 109 s−1 due to spin-orbit coupling (SOC) mediated by the sulfur atoms in combination with a small ΔES1-T1 of ca. 56 meV.
Angewandte Chemie. International edition; 63(7)
Keywords: Carbenes; Circularly Polarized Luminescence; DFT/MRCI; TADF; Zinc; 540